Об этнических стереотипах греков Крыма на рубеже XX-XXI вв. - Араджиони, М.А.; Пригарин, А.А. (Материалы по археологии, истории и этнографии Таврии, 2008)
В настоящей статье нами будет рассмотрена тема этнического самосознания греков Крыма и их этнических стереотипов, пилотное исследование которых проводилось в рамках экспедиций 2001-2002 гг. Выбор именно этого направления исследования был нами сделан не случайно: изучение этнических автостереотипов и гетеростереотипов этносов Крыма в настоящее время является чрезвычайно актуальным для полуострова, который рядом зарубежных и отечественных экспертов признается регионом с высоким конфликтным потенциалом. Some results of the research of ethnic self-actualization of the Greeks in Crimea and their ethnic-actualization and their ethnic stereotypes which was undertaken within ethnographic expeditions in 2001 -2001 are considered in this article. Modern Greek community of Crimea is relatively not very numerous - 3036 (in 2001). The inner structure of the community can be characterized as very complex: under common self-actualization specifics of historic, sociopolitical, regional and sub-ethnic levels remains. Common auto-stereotype of the Greeks living nowadays on the territory of the Crimea can be presented in the following way: religious, industrious, friendly, loving their family, proud, economic, undertaking, and talkative. The first five qualities were mentioned by neighbouring population as characteristic for Greek people. The Greeks demonstrated rather a high level of tolerance, in comparison with the situation in Crimea and Ukraine in general. The presented ethnonimic material enables to trace the history of inter-ethnic contacts of the Greeks of the Crimea, to find out the degree of intensiveness of these contacts, the way these ethno-confession distinctions and some hetero-stereotypes were perceived.